Energy release rate and crack propagation rate behaviour of moisture-deteriorated epoxy adhesives through the double cantilever beam method. Issue 6 (26th April 2023) - Houjou, K.; Sekiguchi, Y.; Shimamoto, K.; Akiyama, H.; Sato, C.
ABSTRACT: In this study, the relationship between the energy release rate ( G 1C ), crack propagation rate (d a /d N ), and the fracture morphology of specimens with deteriorated adhesives after moisture absorption were investigated through the double cantilever beam (DCB) method. The specimens were prepared using a thermosetting epoxy adhesive based on compound carboxyl-terminated butadiene–nitrile rubber and Al 6061-T6 adherends. To accelerate the deterioration of the adhesives, open-faced specimens were immersed in water at 63°C at varying durations. Prior to the assembly of the DCB specimens, the adherends were either treated using acidic solutions or sand blasted. Consequently, the effect of the moisture deterioration of adhesive and the surface treatment performed on the adherend on the fracture morphology was studied. Furthermore, the relationship between G 1C and d a /d N was systematically investigated. At a constant crack opening speed, the failure mode changed from cohesive to interfacial fracture, and then reverted back cohesive fracture as the deterioration of the specimens progressed due to increasing immersion time. Interfacial fracture was not observed for the specimens with sandblasted adherends. Lastly, a decrease in d a /d N was not observed even with increasing G 1C values of the immersed specimens because interfacial fracture was easy to occur when the cyclic strains were applied.